PENGARUH MOTIVASI DAN KEMAMPUAN TERHADAP KINERJA PEGAWAI BAGIAN PENYUSUNAN PROGRAM SEKRETARIAT KABUPATEN PROBOLINGGO - Novi Sri Sandyawati (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2020)
The research objective was to determine the effect of work motivation and ability variables simultaneously on the work performance of employees in the compilation of the Probolinggo district secretariat program, to determine the effect of work motivation and ability variables partially on employee work performance in the regional secretariat programming division of Probolinggo district, to find out which of the variables motivation and ability that have a dominant influence on employee work performance in the regional secretariat programming section of Probolinggo district. The type of research used is the survey method which aims to provide an explanation of the phenomenon under study and the relationship between variables, or in other words it can also be stated that this research is an explanatory study. Hypothesis test 2, namely motivation and ability partially affect the work performance of employees in the preparation of the regional secretariat program of Probolinggo district. The results of the X1 motivation test resulted in a regression coefficient level of b1 = 0.157 with the requirements for the value of tcount> ttable with a value of 1.378> 1.022, and a significance level of α <5% with a result of a significance level of α of 0.018, so partially the motivation variable (X1) had a significant effect. Regarding the work performance of the employees of the regional secretariat programming division of Probolinggo district (Y), the hypothesis can be accepted. The results of the test on the variable X2, the ability to produce a regression coefficient level of b2 = 0.484 with the requirements for the value of tcount> ttable with a value of 3.469> 1022, and a significance level of α <5% with a significance level of α of 0.001, then partially the variable Job Satisfaction (X2 ) has an effect on the work performance of employees in the compilation of the Probolinggo district secretariat program (Y), the hypothesis is acceptable. Hypothesis 3 test, namely the ability to have a dominant effect on employee work performance in the preparation of the Probolinggo district secretariat program is acceptable, this is indicated by the analysis of each variable showing the standardized regression coefficient (β) with the results of the coefficient β2 Ability (X2) is the regression coefficient (β2). = 0.497) the greater the motivation regression coefficient β1 = 0.197 or β2 = 0.497> β1 = 0.197.